Una excusa para pensar en la Teoría General del Derecho del Trabajo: la necesidad de Requerimiento de Pago de las Utilidades - Neves Mujica, Javier (2016)
This article addresses the antinomy concerning to profit sharing to the workers. Through an analysis of the classic criteria of antinomy solutions and particulars of the Labour Law, the author recognize the prevalence of the classic criteria.